Testing some of Benjamin Graham’s Stock Selection Criteria: A Case of the FTSE Bursa Malaysia EMAS Index from Year 2000 to 2009 - Chang, Desmond (Jurnal Manajemen dan Kewirausahaan, 2012)
Benjamin Graham, also known as the “father of value investing” proposed that investment in the stock exchange can be a safe endeavor while receiving gains that outperform the market if the investor makes carefully thought out purchases. This study aims to determine if the use of some of Benjamin Graham’s stock selection criteria is able to generate returns that are significantly greater than the returns in the stock exchange of Malaysia, particularly, the comprehensive FTSE Bursa Malaysia EMAS Index. This study collected secondary data regarding fundamentals of companies listed in the FTSE Bursa Malaysia EMAS Index from the year 2000 to 2009. Five criteria were set up in this research based on one or a combination of price-to-earnings ratio, price-to-book value, current ratio and dividend yield. The listed companies were screened using those criteria. An equally weighted portfolio was created using the screened companies and their one-year and two-year returns calculated. The returns were compared to the market return. Hypotheses of this research were tested using t-test statistic to determine the significance of the data. This research found that most of the screening criteria used generated returns that were higher than the market return in almost every year they were tested in. Benjamin Graham’s stock selection criteria although have been conceived over 80 years ago is still applicable today in the Malaysian market. Further research can be conducted with different criteria with varying holding periods and in different markets.